Apomorphine as an emetic for insectivorous songbirds: effectiveness and post‐release effects on survival and mass change. Issue 2 (June 2014) - Ceresa, Francesco; Belda, Eduardo J.; Monrós, Juan S.
ABSTRACT Emetics can be used to obtain food samples from birds, but they can harm birds during or after treatment. Studies to date suggest that apomorphine is a safe emetic for songbirds, but information is needed about possible post‐release deleterious effects. From March to July 2012, we collected food samples from insectivorous songbirds using apomorphine. We treated 67 Moustached Warblers (Acrocephalus melanopogon), 56 Reed Warblers (Acrocephalus scirpaceus), 15 Great Reed Warblers (Acrocephalus arundinaceus), and 12 Savi's Warblers (Locustella luscinoides). Effectiveness in inducing regurgitation was high (76.7%) and varied among species, being significantly more effective with Reed Warblers (91.1%). No birds died during treatment. To check for possible post‐release negative effects, we considered 53 treated Moustached Warblers and 37 treated Reed Warblers and selected an equal number of untreated individuals (simply captured, banded, and measured). We found no support for differences in survival or recapture probabilities between treated and untreated birds of either species within 21 d after administering apomorphine. We calculated body mass changes of all Moustached Warblers subsequently recaptured (within 21 d) and found no difference between treated (N = 8) and untreated (N = 22) birds, suggesting normal foraging activity after release. Our results suggest that apomorphine is a safe emetic, with no negative effect on survival at least in the short term. The effectiveness of apomorphine with insectivorous songbirds in our study contrasts with the results of some previous studies and confirms the differences in effectiveness among different taxa of songbirds. As with differences in effectiveness among species in our study, this variability in sensitivity to the emetic could be caused by morphological and physiological differences among different taxa.